ANALISIS KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Santika, Suci; Purba, Mortigor Afrizal (SCIENTIA JOURNAL, 2022)
This study aims to analyze managerial ownership and institutional ownership of the value of consumer goods industry companies listed on the Indonesia Stock Exchange and to suppress agency conflicts that are obstacles to achieving their goals. This study uses quantitative methods based on multiple linear regression analysis between managerial ownership and institutional ownership on firm value obtained Y = -191294863.181 + 0.240X1 + (-1385552.932)X2 + e. The results of the t-test of this study indicate that managerial ownership has a significant effect on firm value while institutional ownership has no significant effect on firm value. The results of the f test show that managerial ownership and institutional ownership have a significant effect on firm value, while the coefficient of determination from Adjusted R Square is 0.286 or the ability of the independent variable to explain the dependent variable is 28.6%.